Investigating the structural transformation of individual Au-incorporated carbon nanofiber interconnect - Rosmi, Mohamad Saufi; Yaakob, Yazid; Mohd Yusop, Mohd Zamri; Md Isa, Illyas; Sidik, Siti Munirah; Abu Bakar, Suriani; Masaki, Tanemura (Universiti Putra Malaysia, 2022)
Nowadays, a smaller electronic integrated circuit demands a smaller width and pitch of interconnect. Copper (Cu) interconnect, which is currently the most common, suffers from the size effect and grain boundary scattering. Hence, carbon materials such as carbon nanotubes (CNTs) and carbon nanofiber (CNF), as well as their nanocomposites are potential replacement materials for Cu interconnects. However, the interaction of carbon atoms and its metal catalyst is quite critical for obtaining nanocarbon structure with precise layer number, crystal size and structure. Here, an in-situ transmission electron microscopy (TEM) observation of graphitic hollow structure growth from a single Au-incorporated carbon nanofiber (Au-CNF) during current-voltage (I-V) measurement is demonstrated. With an applied potential in a two-probe system, significant structural change of Au-CNF was discovered. Due to Joule heating and a considerable temperature gradient, the Au nanoparticles agglomerated and evaporated under high current flow ranging from 1.35 to 18.7 µA. The TEM images and electron diffraction pattern revealed that after the current flow, the amorphous carbon structure of CNF was converted to a hollow sp2 graphitic carbon structure catalyzed by dispersed Au particles. The graphitic carbon structure, however, collapsed in the center at a higher applied potential of 60 A due to excessive current flow and induced Joule heating. The direct observation of graphene synthesis thru in-situ TEM is important for revealing the solid phase interaction of Au and carbon atoms.